2018
DOI: 10.3390/ijerph15102144
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Violence Impacts Disease Control and Surveillance: Case Study of Cali, Colombia from 2014 to 2016

Abstract: Arboviruses are responsible for a large burden of disease globally and are thus subject to intense epidemiological scrutiny. However, a variable notably absent from most epidemiological analyses has been the impact of violence on arboviral transmission and surveillance. Violence impedes surveillance and delivery of health and preventative services and affects an individual’s health-related behaviors when survival takes priority. Moreover, low and middle-income countries bear a disproportionately high burden of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
(116 reference statements)
1
4
1
Order By: Relevance
“…As in other studies, the northern Caribbean region of Colombia, represented in our study by Barranquilla, was the most affected [34,40–42]. However, in contrast to previously published findings [40,43–46], the southwest (Cali) and northeast (Bucaramanga and Cúcuta) had fewer reported cases in our study. This could be because at the time of patient assessment in those cities, the CHIKV epidemic had just started (end of 2014), while the published findings from those regions are from the peak of the epidemic in early and mid-2015.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…As in other studies, the northern Caribbean region of Colombia, represented in our study by Barranquilla, was the most affected [34,40–42]. However, in contrast to previously published findings [40,43–46], the southwest (Cali) and northeast (Bucaramanga and Cúcuta) had fewer reported cases in our study. This could be because at the time of patient assessment in those cities, the CHIKV epidemic had just started (end of 2014), while the published findings from those regions are from the peak of the epidemic in early and mid-2015.…”
Section: Discussioncontrasting
confidence: 68%
“…A recent study conducted in Barranquilla showed that the CHIKV epidemic affected mostly the poorest communities [34]. Moreover, in a study from Cali the authors observed clustering of homicide rates, lower social strata, and increased risk of arboviral infections (CHIKV and dengue), supporting the hypothesis that reported violence impacts disease risk [43]. Another study in two neighbouring municipalities from the northern region of the country demonstrated that a high number of families with low income in one municipality was associated with high health vulnerability [41].…”
Section: Discussionmentioning
confidence: 80%
“…[22][23][24] Recent ecologic studies have shown a substantial impact of violence on arboviral surveillance activities conducted in the same zone of the city, highlighting the importance of integrating measures of social disparities and conflict into reports of case finding for infectious diseases. 25,26 Another recent study, conducted in a violent, overcrowded urban slum in Brazil, demonstrated that training and hiring community members to deliver TB services increased treatment success and cure proportions among TB patients from that community. 27 The Secretary of Health of Cali could consider a similar strategy of hiring (or involving volunteers) local residents to perform contact investigation activities in the western zone.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of being able to see, and then map, the local drainage channel, a local or expert voice can tell how the trash being dumped is the cause of local flooding [ 22 ], or how there are still mosquito clouds in the dry season because of the trapped standing water, or why residents distrust the local hospital [ 34 ]. In Colombia, these geonarratives helped explain localized patterns of dengue [ 36 ], and also the connected issue of violence [ 39 ]. In Cambodia, flooding in the informal settlements was described in terms of the individual impact it would have as the feces-tainted water would rise within the home during the rainy season.…”
Section: Introductionmentioning
confidence: 99%